MSH2 shapes the meiotic crossover landscape in relation to interhomolog polymorphism in Arabidopsis. (16th September 2020) - Blackwell, Alexander R; Dluzewska, Julia; Szymanska‐Lejman, Maja; Desjardins, Stuart; Tock, Andrew J; Kbiri, Nadia; Lambing, Christophe; Lawrence, Emma J; Bieluszewski, Tomasz; Rowan, Beth; Higgins, James D; Ziolkowski, Piotr A; et al.
Abstract: During meiosis, DNA double‐strand breaks undergo interhomolog repair to yield crossovers between homologous chromosomes. To investigate how interhomolog sequence polymorphism affects crossovers, we sequenced multiple recombinant populations of the model plant Arabidopsis thaliana . Crossovers were elevated in the diverse pericentromeric regions, showing a local preference for polymorphic regions. We provide evidence that crossover association with elevated diversity is mediated via the Class I crossover formation pathway, although very high levels of diversity suppress crossovers. Interhomolog polymorphism causes mismatches in recombining molecules, which can be detected by MutS homolog (MSH) mismatch repair protein heterodimers. Therefore, we mapped crossovers in a msh2 mutant, defective in mismatch recognition, using multiple hybrid backgrounds. Although total crossover numbers were unchanged in msh2 mutants, recombination was remodelled from the diverse pericentromeres towards the less‐polymorphic sub‐telomeric regions. Juxtaposition of megabase heterozygous and homozygous regions causes crossover remodelling towards the heterozygous regions in wild type Arabidopsis, but not in msh2 mutants. Immunostaining showed that MSH2 protein accumulates on meiotic chromosomes during prophase I, consistent with MSH2 regulating meiotic recombination. Our results reveal a pro‐crossover role for MSH2 in regions of higher sequence diversity in A. thaliana . Synopsis: Meiotic DNA double‐strand breaks undergo interhomolog repair to yield crossovers between homologous chromosomes. Sequencing of polymorphisms in wild‐type and mutant plants reveals an unexpected pro‐crossover role of the mismatch repair protein MSH2 in regions of higher relative sequence diversity. Meiotic crossovers are positively associated with interhomolog polymorphism both at chromosome level and fine scales in Arabidopsis. Class I crossovers mediate association of recombination with diversity – although very high polymorphism levels suppress crossovers. Total crossover numbers are unchanged in msh2 mutants, but recombination is remodelled from the diverse pericentromeres towards the less polymorphic sub‐telomeres. Juxtaposition of megabase‐scale heterozygous and homozygous regions causes crossover remodeling towards the heterozygous regions, which is MSH2‐dependent. Abstract : Sequencing of polymorphisms between homologous chromosomes in wild‐type and mutant plants reveals an unexpected pro‐crossover role of the mismatch repair protein MSH2 in regions of higher relative sequence diversity.